Case Report: Intravitreal dexamethasone implant as adjuvant treatment for taxane-related cystoid macular edema - Liu, Xujia; Ding, Xiaohua; Lin, Guoqiao (Frontiers in Ophthalmology, 2022)
Taxane-related cystoid macular edema (CME) is a rare complication of the taxoid medication, a chemotherapeutic drug. We report a 47-year-old Han Chinese man referred to our Eye Center for decreased vision with visual distortion in both eyes for two weeks. Two weeks prior, he received the last cycle of his six-monthly chemotherapy, including paclitaxel for hypopharyngeal malignancy. The best-corrected visual acuity (BCVA) was 0.4 OD and 0.1 OS. Macular optical coherence tomography showed significant bilateral CME, and fluorescein angiography (FA) revealed the fluorescein pooling at the late phase without leakage. Intravitreal 700 μg dexamethasone (DEX) implant was applied to the left eye and 13 days after to the right eye. Two months later, the macular morphology recovered to normal. One year after the first visit, the BCVA was 1.0 OD and 0.8 OS with standard macula on OCT. In conclusion, the intravitreal DEX implant might be an effective adjuvant treatment for taxane-related CME.